The covid-19 in India- impacts on the economy and the automobile sector - P B, MRS. LAVANYA; THUNGA, DR. SUBBA RAYUDU; RAJU, DR. N. Y. (The journal of contemporary issues in business and government, 2021)
This paper demonstrates the impact of lockdown in Indian economy particularly on automobile sector. The outcome proves that depending on the period of the lockdown, the Indian economy expected to face a loss of about 10-31% of its Gross Domestic Product and production loss is estimated on automobile sector is Rs 2300 crore per day. This study discusses the impact of covid-19 on economy, particularly on automotive sector. This is a secondary research work wherein aim is to study the potential impact of the novel covid-19 on automotive sector. The methodology adopted includes in-depth review and analysis of various reputed published journals, research works, articles, news paper reports and web sources. The study concludes that impact of corona virus is long term and adverse. It is the turn of Indian automotive industry to grab opportunities and flourish.